1008 ENDOTHELIAL CELL-DERIVED MICROPARTICLES FROM OBSTRUCTIVE SLEEP APNEA HYPOXIA SYNDROME PATIENTS INCREASE HUMAN AORTIC ENDOTHELIAL CELL PERMEABILITY AND DYSFUNCTION. (28th April 2017) - Jia, L; Lau, WB; Ma, X; Du, J; Nie, S; Wei, Y
Abstract: Introduction: Obstructive sleep apnea hypoxia syndrome (OSAHS) is an independent risk factor for coronary artery disease (CAD). Treatment of OSAHS improves clinical outcome in some CAD patients, but the relationship between OSAHS and CAD is complex. Microparticles (MPs) are shed by the plasma membrane by either physiologic or pathologic stimulation. Here we investigated the role of MPs in the context of OSAHS. Methods: Patients with both suspected coronary artery stenosis and OSAHS were enrolled and underwent both coronary arteriography and polysomnography. 53 total patients in this study underwent cardiac angiography and PSG, and were divided into 3 groups per cardiac vessel stenosis extent and apnea/hypopnea index (AHI): 1) Control group, characterized by stenosis<50% and AHI<5; 2) CAD group: stenosis≥70% and AHI<5; 3) CAD+OSAHS group: stenosis≥70% and AHI>15. Circulating MPs were isolated from plasma and analyzed by flow cytometry. For permeability assay, FITC-CM-dextran was added in the upper channel after human aortic endothelial cells (HAECs) being stimulated with MPs in the transwell system. Results: 53 patients were included in the present study, and there was no statistically significant demographic difference (age, sex, BMI, biological data, tobacco abuse, diabetes comorbidity) between the 3 groups. The AHI and 4% oxygen desaturation index (ODI) in the CAD+OSAHS group were significantly greater compared to both the control and CAD groups. Moreover, the mean SaO2 in the CAD+OSAHS group was decreased compared to the two other groups. CAD+OSAHS patients exhibited greater levels of total MPs (Annexin V + ), erythrocyte-derived MPs (CD235 + Annexin V + ), platelet-derived MPs (CD41 + Anexin V + ), and leukocyte-derived MPs (CD144 + Annexin V + ) compared to CAD alone patients or control. CAD+OSAHS patients expressed the greatest level of endothelial-derived MPs of all cellular origin types (CD144 + Annexin V + ). Treatment of human aortic endothelial cells (HAECs) with MPs isolated from CAD+OSAHS patients markedly increased HAEC permeability, and significantly upregulated mRNA levels of ICAM-1, VCAM-1, and MCP-1. Conclusion: OSAHS+CAD patients harbor increased levels of MPs, particularly the endothelial cell-derived subtype. When administered to HAECs, OSAHS+CAD patient MPs increase endothelial cell permeability and dysfunction. Support (If Any): International Science & Technology Cooperation Program of China(2015DFA30160).